Efficiency of personal dosimetry methods in vascular interventional radiology - Bacchim Neto, Fernando Antonio [UNESP] (2017)
Purpose The aim of the present study was to determine the efficiency of six methods for calculate the effective dose (E) that is received by health professionals during vascular interventional procedures. Methods We evaluated the efficiency of six methods that are currently used to estimate professionals’ E, based on national and international recommendations for interventional radiology. Equivalent doses on the head, neck, chest, abdomen, feet, and hands of seven professionals were monitored during 50 vascular interventional radiology procedures. Professionals’ E was calculated for each procedure according to six methods that are commonly employed internationally. To determine the best method, a more efficient E calculation method was used to determine the reference value (reference E) for comparison. Results The highest equivalent dose were found for the hands (0.34 ± 0.93 mSv). The two methods that are described by Brazilian regulations overestimated E by approximately 100% and 200%. The more efficient method was the one that is recommended by the United States National Council on Radiological Protection and Measurements (NCRP). The mean and median differences of this method relative to reference E were close to 0%, and its standard deviation was the lowest among the six methods. Conclusions The present study showed that the most precise method was the one that is recommended by the NCRP, which uses two dosimeters (one over and one under protective aprons). The use of methods that employ at least two dosimeters are more efficient and provide better information regarding estimates of E and doses for shielded and unshielded regions.